Upaya yang Dapat Dilakukan dalam Menanggulangi Pencemaran Udara oleh Limbah Industri - Umairoh, Putri Suci; Gusmira, Eva (Lembaga Yasin AlSys, 2024)
Jambi is a province where most of its wealth comes from agricultural products,where these agricultural products must be processed first so that the raw agricultular products produced can become a product of higher quality and selling price which can be marketed and used well and efficiently.globally and for ordinary people,all of this can happen with the help of industry.menwhile,the waste produced by this industry causes pollution to the environment,one of which causes air pollution which result in various diseases for local peole such as respirstory problems and so on.This jurnal was written with the aim of to advise readers,especially the authorities,what efforts they can take to reduce the effects of industrial waste on air pollution.The data collection method used secondary data collection techniques take from the meteorology,climatology and geophysics agency.used to measure air quality in the form of the GAIA air quality sensor.the measurement result show that the level of air pollution in jambi is currently at a moderate level with an air quality index reching 89 AQI US compared to other regions in Indonesia.jambi is ranked 7th after pekan baru,riau.based on the air quality for jambi,it can be concluded that on June 15 2024 at 7 and 10 am and 12 to 1 pm the air quality is underhealthy as well as PM2.5 and for PM10 and ozone measurements it shows good value level.